DEVELOPMENT OF VALUE ADDED PRODUCTS FROM SHODDY YARN - Gupta, Mohini (International Journal of Research -GRANTHAALAYAH, 2016)
This study was undertaken for development of value added products from shoddy yarn (Recycled yarn). For the study, shoddy yarns were collected from Ludhiana and Amritsar districts of Punjab for preparing the fabric. Two count of shoddy yarn i.e. 10Nm and 12Nm were selected for the product development. Twenty four prototype samples were designed, from which six most preferred design was obtained for development of value added product from developed fabric then consumer acceptability were assessed and found that majority of the respondents preferred the developed products.